Psychometric properties of the Slovenian adaptation of the Revised Generic Occupational Stress Index Questionnaire (RG-OSI) - Nataša Sedlar; Gregor Sočan; Lilijana Šprah (Psihološka Obzorja, 2014)
The Revised Generic Occupational Stress Index questionnaire (RG-OSI) employs the cognitive ergonomics approach that quantifies the burden of stressors on cognitive resources of the employee. The model is structured as a 2-dimensional matrix, where each element is scored from 0 to 2 (sometimes with intermediate values of 0.5, 1.5 or 1.75) as a combination of various items based on multiple criteria. Due to uncommon scoring system of the questionnaire, our study aimed to explore the appropriateness of the existing scoring system and to get some information on validity of the scale on a Slovenian sample. The questionnaire has been applied on 349 Slovenian employees from different occupational groups and the data were analysed by means of correspondence analysis, classical reliability and item analysis and item response theory analysis. The results of correspondence analysis demonstrate that the response categories on individual variables are not always ordered. Furthermore, we conducted reliability analysis for scales, developed short versions of the scales, and obtained some preliminary information on their validity. The current study provides evidence that the described original scoring system in psychological measures may not be appropriate from the psychometric viewpoint.